Young people engaging in event-based diaries: A reflection on the value of diary methods in higher education decision-making research. (June 2023) - Baker, Zoe
This paper reflects on the value of diary methods in the context of a qualitative, longitudinal narrative inquiry exploring the higher education decision-making of further education students in England. Event-based diaries were used alongside interviews and focus groups over a 14-month period to gain in-depth insights into the reasons and influences informing their decision-making trajectories. I explore the challenges, successful approaches and advantages of employing diary methods with young people in this context. Challenges consisted of maintaining participant engagement, which was overcome by combining methods and incorporating a reactive co-participatory element. Yet, a number of advantages emerged from participants' engagement with diary keeping which enhanced the richness of the data; this inspired deeper reflections on decision-making and influences and provided a private space for participants to disclose personal difficulties that could not be obtained via interviews.